Fabrication and characterization of polyvinylidene fluoride composite nanofiber membrane for water flux property - Mohd. Zahari, Azizul (Penerbit UTM Press, 2015)
This research is about the investigation of the pure water flux property of composite polyvinylidene fluoride (PVDF) nanofibers. Electrospinning technique was used to prepare the composite electrospun nanofibers. PVDF was dissolved in N,N-dimethylformamide (DMF) solvent and blended together with activated carbon (AC) and polyvinylpyrrolidone (PVP). The nanofibers were characterized to determine the morphologies, wettability property, and its tensile strength. The fabricated nanofibers diameter was found in the range between 20 to 180 nm. The presence of AC deteriorates the mechanical properties of the nanofibers as the size of AC is larger than the external diameter of the nanofibers. The results of contact angle confirmed that the fabricated nanofiber exhibit less hydrophobic in the presence of PVP and AC. The less hydrophobic